Developing mobile-augmented reality in higher learning education / Aslina Baharum … [et al.] - Baharum, Aslina; Frederick Bulagang, Aaron; Mohd. Rusli, Nordalieia; Soo Fun, Tan; Hanapi, Rozita (Division of Research and Industry Linkages, 2017)
Mobile learning has contributed effectively at various Universities in Malaysia since its implementation. Mobile Learning is defined as the use of a mobile or wireless device for learning purpose while giving mobility. Mobile learning concept starts from e-learning that slowly develops into mobile learning as technology improved over the decades. Augmented reality or well-known as AR combines real environment with a virtual object that users can interact with, with a mobile device such as Smartphone and tablet that are powerful enough to support augmented reality, mobile-Augmented Reality is possible to be used in education. Using mobile-Augmented Reality in education can help gain interest from students during the learning session. The current problem with mobile learning is the visualization and content presented in the application, where it may not be appealing for the student to use because it is mostly text-based. Next issue regarding mobile learning is the user interface where it may not be usable to a non-experience user, and most important is the framework available for mobile-Augmented Reality is still limited. The aim of developing a mobile learning application is for teaching and learning method that to motivate students to learn through the use of their smart phones. This project focuses on developing a mobile learning and a mobile-Augmented reality application for learning Network Fundamental courses offered to Computer Science students. The application developed involved learning material such as the 7 OSI Layers, the port labels for networking device for Router, Switch and their configurations.